SIKAP DAN PENGAMBILAN KEPUTUSAN KONSUMEN DALAM MEMBELI BUAH JERUK LOKAL DAN JERUK IMPOR DI BANDAR LAMPUNG - Mellyssa Jumiana Rajagukguk; Wuryaningsih Dwi Sayekti; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This research aimed to determine the consumer attitude towards a decision to buy local and imported oranges, the purchase pattern of consumer towards local and imported oranges, and the factors that influence the purchased amount of oranges in Bandar Lampung. The research was conducted on purpose intraditional and modern markets in Bandar Lampung, i.e. Tugu Market, Koga Market, Way Halim Market, Pasir Gintung Market, SMEP Market, Tamin Market, Rajabasa Market, Panjang Market, Cimeng Market, Kangkung Market, Chandra Tanjung Karang supermarket, Robinson supermarket, Gelael, and Istana Buah.The total samples were 100 respondents. The samples were selected by accidental sampling method. The reasearch data was collected in February to March 2013 by the survey method. The data was analyzed by Multiatribut Fishbein analysis and multiple linear regression analysis. The results of this research showedthat the consumer preffered the attributes of imported oranges compared to local oranges. The types of oranges purchased by consumers were Medan oranges as local oranges and Mandarin Ponkam as imported oranges. The average frequency of oranges buying was three times per month, and the number of purchase amount was four kilograms per month. The factors that influenced the purchase of oranges were the household income and family size.Key words: consumer attitude, Multiatribut Fishbein analysis, oranges, purchase pattern